2007
DOI: 10.1002/prca.200600288
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of alpha‐1‐antitrypsin in immunoglobulin A nephropathy

Abstract: Immunoglobulin A nephropathy (IgAN) is recognized as the most common form of primary glomerulonephritis worldwide. It is characterized by mesangial cell proliferation with mesangial IgA deposition in the glomeruli, and is usually associated with secondary tubulointerstitial injury. Although significant progress has been made in the clarification of the pathogenesis of IgAN, the exact pathogenetic mechanism remains unclear. To find out the candidate proteins that play an important role in IgAN, renal cortex tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…Accumulating studies have showed that AAT may lead to lung pathologies [68], type 1 diabetes [69], arthritis [70], and lupus [71]. Kwak et al [72] found that the expression of AAT is elevated in renal biopsies, while other investigators detected that it is overexpressed in the urine of some renal diseases [7375]. This phenomenon was consistent with our result in which AAT was upregulated.…”
Section: Discussionsupporting
confidence: 92%
“…Accumulating studies have showed that AAT may lead to lung pathologies [68], type 1 diabetes [69], arthritis [70], and lupus [71]. Kwak et al [72] found that the expression of AAT is elevated in renal biopsies, while other investigators detected that it is overexpressed in the urine of some renal diseases [7375]. This phenomenon was consistent with our result in which AAT was upregulated.…”
Section: Discussionsupporting
confidence: 92%
“…These explanations are speculative but are fitting at a conceptual level and have been mentioned here to highlight the significance of the human urinary database in a way that opens a door for further investigation whereby researchers of all disciplines are invited to participate. ␣ 1 -Antitrypsin and its fragments were reported to be upregulated in several types of CKD (57,63,68,69). Thus, increased urinary excretion of a fragment of this highly abundant plasma protein, together with fragments derived from serum albumin and fibrinogen, may reflect chronic renal damage.…”
Section: Table I Demographic Data Of All Patients Used In This Studymentioning
confidence: 99%
“…Kwak et al [40] reported increased levels of A1AT peptides in kidney tissue and urine in IgAN patients compared with healthy subjects. The authors speculated that renal tubular epithelial cells produce A1AT in response to tubulointerstitial damage.…”
Section: Discussionmentioning
confidence: 99%